Optimasi Proses Ozonasi Untuk Penurunan Kadar Krom (Cr) dalam Limbah Cair Elektroplating dengan Metode Respon Permukaan - Aji Prasetyaningrum; M. Djaeni; Bakti Jos; Yudhy Dharmawan (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
Industrial wastewater from electroplating process containing the heavy metals, such as Chromium (Cr). The initial content of Cr in electroplating waste water was approximately 78.24 ppm. The Cr content may be discharged into waters and safe for the environment is 2 ppm.Industrial electroplating waste water usually treated with a combination of chemical and physical processes such as coagulation and flocculation. However, conventional processing system requires a long of processing time and a large area. This study aims to provide an alternative treatment of electroplating wastewater through the application of ozonation technology. Response Surface Methodology was used to obtain optimum conditions in decreased levels of Cr content. Variable for ozonation process included of ozonation time (X1), pH (X2) and ozone gas flow rate (X3). The results showed that the effectiveness of ozonation treatment increase at lower pH. The high value of correlation (R2 = 0.93767) indicated that a high correlation values between the experimental and prediction data. The optimum conditions for Cr degradation at 30 minutes of ozonation treatment, pH 2 and ozone gas flow rate of 3 L min-1, with the lowest contentration of Cr was 1.92 ppm.